GE_GERICHTE P/7821/2025 vom 27. Juni 2025 - GE Cour de justice (2025)
PERQUISITION DE DOCUMENTS ET ENREGISTREMENTS;SÉQUESTRE(MESURE PROVISIONNELLE);SCELLÉS;DÉCISION D'IRRECEVABILITÉ | CPP.197; CPP.263